Strategy to Increase Elementary School Students’ Interest in Geography through Children’s Atlas Learning to Encourage the Development of Spatial Marketing for MSMEs in Lemahbang Village, Kismantoro District, Wonogiri Regency - Purwanta; Dewi, Pramitha (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
Lemahbang Village, Kismantoro District, Wonogiri Regency, Central Java has a variety of potential resources to support local economic growth through Micro, Small and Medium Enterprises (MSMEs). The potential of MSMEs in Lemahbang Village, more precisely Lemahbang Hamlet and Janggle Hamlet, needs to be introduced to the wider public through digital media to increase product engagement and the profile of Lemahbang Village itself. Today, all forms of information can be presented and disseminated using technology. In an era that cannot be separated from questions about location like today, the marketing technique of a product inevitably collaborates with Geographic Information System (GIS) technology to create a new breakthrough called spatial marketing. The UGM KKN-PPM Team created a digital printed map and web mapping application which are expected to be able to become a digital promotional media for MSMEs in Lemahbang Village. GIS is a child of the parent science of Geography which can be collaborated with various other scientific disciplines so that it has been widely used in various sectors. These advantages make GIS important to study in order to increase the number of Geospatial Information experts in Indonesia. This can be started from the basics by instilling an interest in elementary school students towards Geography. In order to achieve this, the UGM KKN-PPM Team created a fun learning-based Atlas Anak learning work program for fifth and sixth grade students of SD Negeri 1 Lemahbang.